2012
DOI: 10.1371/journal.pone.0031316
|View full text |Cite
|
Sign up to set email alerts
|

Integrated HIV Testing, Malaria, and Diarrhea Prevention Campaign in Kenya: Modeled Health Impact and Cost-Effectiveness

Abstract: BackgroundEfficiently delivered interventions to reduce HIV, malaria, and diarrhea are essential to accelerating global health efforts. A 2008 community integrated prevention campaign in Western Province, Kenya, reached 47,000 individuals over 7 days, providing HIV testing and counseling, water filters, insecticide-treated bed nets, condoms, and for HIV-infected individuals cotrimoxazole prophylaxis and referral for ongoing care. We modeled the potential cost-effectiveness of a scaled-up integrated prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 44 publications
(59 reference statements)
1
49
0
Order By: Relevance
“…Cost-effectiveness analyses showed that 191 disability-adjusted life years (DALYs) and US$48,123 per 1,000 participants could be averted through the provision of the US$20 water filters to HIV-infected individuals. 33,34 These data also suggest that there may be added benefit of simple home visitations to reinforce the use of the device; however, we do not have estimates on the cost effectiveness of such services. This type of reinforcement is likely cost effective only in settings where participants live within a reasonable distance from health facilities.…”
Section: Discussionmentioning
confidence: 93%
“…Cost-effectiveness analyses showed that 191 disability-adjusted life years (DALYs) and US$48,123 per 1,000 participants could be averted through the provision of the US$20 water filters to HIV-infected individuals. 33,34 These data also suggest that there may be added benefit of simple home visitations to reinforce the use of the device; however, we do not have estimates on the cost effectiveness of such services. This type of reinforcement is likely cost effective only in settings where participants live within a reasonable distance from health facilities.…”
Section: Discussionmentioning
confidence: 93%
“…Details of the model have been published elsewhere 8. The model estimates the health and cost benefits of prevention for malaria, diarrhoea and HIV separately.…”
Section: Methodsmentioning
confidence: 99%
“…Those testing positive for HIV were offered on-site CD4 count determination, cotrimoxazole prophylaxis and referral to comprehensive HIV care and treatment. The campaign yielded large health benefits and net economic savings 7 8. Large-scale expansion of this integrated prevention campaign (IPC) has the potential to deliver substantial health benefits and cost savings.…”
Section: Introductionmentioning
confidence: 99%
“…Findings were robust to the sensitivity analyses performed. Kahn et al 37 concluded a more “favorable outcome” in their study, compared with the CE of existing published findings regarding malaria prevention–related interventions (a cost ranging from $2 to 15 per DALY averted 44 ).…”
Section: Resultsmentioning
confidence: 84%
“…Kahn et al 37 (2012), a level 1–rated study, addressed the CE of the aforementioned “Integrated Prevention Campaign” using a “spreadsheet-based model.” Existing data regarding the impact of the each of the 3 assessed interventions (VCT, LLINs, and water filters) on morbidity and mortality, along with the available costing information from the same campaign (in the study of Kahn et al 2011), were used to determine estimates of averted deaths, DALYs, and cost savings. The model-based analysis included added costs associated with potential earlier ART initiation as well.…”
Section: Resultsmentioning
confidence: 99%